Solid Dispersion Technology for Improving the Solubility of Antiviral Drugs - Butar-Butar, Maria Elvina Tresia; Wathoni, Nasrul; Ratih, Hestiary; Wardhana, Yoga Windhu (Pharmaceutical Sciences and Research, 2023)
Most drugs, including antiviral drugs, show low solubility in water, which affects dissolution, bioavailability, and therapeutic effectiveness. Therefore, many antiviral drugs are given in very large doses. One of the efforts to overcome these problems is the application of solid dispersions in which polymers and surfactants can trap drug molecules that are in the amorphous phase. Drugs in a hydrophilic carrier will increase wettability, water absorption capacity, and porosity of particles, so that the drug is released better. This review article will discuss the development of technology in solid-state, how solid dispersion overcomes the lack of solubility and the rate of dissolution of antiviral drugs, and solid dispersion preparation techniques. We also discuss some examples of successful applications of solid dispersion methods to antiviral drugs that have been circulating on the market. Overall, this review article offers information of innovation in the development of antiviral drugs to provide more solid dispersion antiviral drug products.